2009
DOI: 10.1021/bm8014522
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relations of Nanolipoblockers with the Atherogenic Domain of Human Macrophage Scavenger Receptor A

Abstract: Oxidized low density lipoprotein (oxLDL) uptake by macrophages is mediated by scavenger receptors and leads to unregulated cholesterol accumulation. Micellar nanolipoblockers (NLBs) consist of alkyl chains and polyethylene glycol on mucic acid. NLBs functionalized with anionic groups inhibit oxLDL uptake via the scavenger receptor A (SR-A). Molecular modeling and docking approaches were used to understand the structure-activity relationship (SAR) between NLBs and SR-A. Six NLB models were docked to the SR-A ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
53
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 45 publications
7
53
0
Order By: Relevance
“…Targeting ligands can be immunogenic and may not be able to confer the broad-spectrum specificity to varying stages of plaque development seen with AM NPs (28). In contrast, the nanoscale presentation of AMs via the NPs elevates the net binding affinity of the AMs for SRs, leading to enhanced lesion retention and association with macrophages and activated endothelia (14). AM NP targeting may also occur because of the damaged endothelial lining covering plaques, enabling enhanced permeability and retention of nanoscale particles (6,29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Targeting ligands can be immunogenic and may not be able to confer the broad-spectrum specificity to varying stages of plaque development seen with AM NPs (28). In contrast, the nanoscale presentation of AMs via the NPs elevates the net binding affinity of the AMs for SRs, leading to enhanced lesion retention and association with macrophages and activated endothelia (14). AM NP targeting may also occur because of the damaged endothelial lining covering plaques, enabling enhanced permeability and retention of nanoscale particles (6,29).…”
Section: Discussionmentioning
confidence: 99%
“…By decreasing lipid accumulation within the artery, local inflammation would be lower and result in an overall reduction in artery occlusion. In contrast to AM NP-treated mice, the histology of lesions in animals treated with control PS 14 PEG NPs did not show reduced lipid and inflammatory burden (SI Appendix, Fig. S9).…”
Section: Nps Lower Artery Occlusion By Reducing Lipid Accumulation Nmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous research has shown the importance of downregulating macrophage scavenger receptors, as they exacerbate the inflammatory pathway in atherosclerosis [29]. As oxLDL uptake by scavenger receptor is also a critical step in the SMC proliferation pathway, we sought to specifically design AM systems to counteract oxidative stress leading to restenosis and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that pharmaceutical agents like apoA-I mimetic peptides, whose primary use is to raise serum levels of atheroprotective HDL and reverse atherosclerosis by lowering lipid loads within the vasculature, may also have beneficial effects by blocking SR-dependent macrophage adhesion, thereby facilitating egress of macrophages from the plaque (Neyen et al 2009). Similarly, a recent nanoscale approach blocking oxLDL binding to SRs in order to reduce foam cell formation has generated so-called nanolipoblockers functionalized with anionic groups, which mimic SR-A ligands, bind to the collagenous domain and show some promise in efficient out-competition of oxLDL (Plourde et al 2009). Comparable objectives have been reached for CD36, where a high-throughput screen for small-molecule inhibitors of modified LDL uptake identified two promising leads with micromolar IC 50 that may antagonize foam cell formation (Xu et al 2010).…”
Section: Discussionmentioning
confidence: 99%